Emerging Roles of Circular RNAs in Thyroid Cancer - Xia, Fada; Zhang, Zeyu; Li, Xinying (Frontiers in Cell and Developmental Biology, 2021)
Thyroid cancer (TC) has the highest incidence among endocrine malignancies. Thus, it is essential to achieve a deep understanding of various mechanisms of development and progression of TC . circRNAs are recognized by multiple studies as being dysregulated in TC. Accumulating evidences have revealed that circRNA serve as a regulatory molecules involving in various biological processes in TC, including cell proliferation, apoptosis, invasion/migration, metabolism and chemoresistance. Furthermore, circRNA can also serve as an effective tool in TC researches of diagnosis, prognosis and treatments. Thus, this review is to outline the characteristics of circRNAs, generalize their categories and functions, and highlight the expression of circRNAs in TC. Meanwhile, we are expecting to achieve a comprehensive understanding of new therapies based on circRNAs in treating or preventing TC.